A Fatwa DSN-MUI Tentang Dropship Menurut Perspektif Sosiologi Antropologi - Kholid Anwar; Tajul Arifin; Dedeh Jubaedah (CV. ITTC INDONESIA, 2025)
Abstract This study examines the implementation of the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) on dropship practices in the context of e-commerce, focusing on the Shopee platform. Using a descriptive qualitative approach and desk research method, this study analyzes the conformity of the dropship mechanism at Shopee with the sharia principles outlined in DSN Fatwa No.145/DSN-MUI/XII/2021. The analysis is conducted through a sociological perspective of legal anthropology to understand the social and legal implications of the implementation of the fatwa. The results show that the practice of dropshipping in Shopee has generally met the characteristics set out in the DSN-MUI fatwa, both in mechanisms with supplier permission and without permission. However, the implementation of this fatwa faces challenges in the aspects of positive law legitimacy and practice standardization. This study also reveals the evolution of sharia dropship regulation in Indonesia, which includes the stages of introduction, recognition, and refinement. The role of DSN-MUI as the sole authority in issuing fatwas on sharia economics is identified as a key factor in promoting uniformity of standards and sharia legitimacy in e-commerce practices. This research contributes to a more comprehensive understanding of the interaction between Islamic law, digital economic practices and the needs of Indonesian Muslim society in the context of e-commerce. The practical implications of this study include recommendations for the standardization of sharia dropship practices and the enhancement of fatwa adoption mechanisms into formal regulations to strengthen a sustainable sharia e-commerce ecosystem. Keywords: Dropship, E-commerce, Fatwa DSN-MUI, Shopee, Sharia Economics, Sociology of Legal Anthropology Abstrak Penelitian ini mengkaji implementasi fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) tentang praktik dropship dalam konteks e-commerce, dengan fokus pada platform Shopee. Menggunakan pendekatan kualitatif deskriptif dan metode penelitian kepustakaan, studi ini menganalisis kesesuaian mekanisme dropship di Shopee dengan prinsip-prinsip syariah yang digariskan dalam Fatwa DSN No.145/DSN-MUI/XII/2021. Analisis dilakukan melalui perspektif sosiologi antropologi hukum untuk memahami implikasi sosial dan hukum dari penerapan fatwa tersebut. Hasil penelitian menunjukkan bahwa praktik dropship di Shopee secara umum telah memenuhi karakteristik yang ditetapkan dalam fatwa DSN-MUI, baik dalam mekanisme dengan izin supplier maupun tanpa izin. Namun, implementasi fatwa ini menghadapi tantangan dalam aspek legitimasi hukum positif dan standardisasi praktik. Studi ini juga mengungkapkan evolusi regulasi dropship syariah di Indonesia, yang meliputi tahap pengenalan, pengakuan, dan pemurnian. Peran DSN-MUI sebagai otoritas tunggal dalam mengeluarkan fatwa ekonomi syariah diidentifikasi sebagai faktor kunci dalam mendorong keseragaman standar dan legitimasi syariah dalam praktik e-commerce. Penelitian ini berkontribusi pada pemahaman yang lebih komprehensif tentang interaksi antara hukum Islam, praktik ekonomi digital, dan kebutuhan masyarakat Muslim Indonesia dalam konteks e-commerce. Implikasi praktis dari studi ini mencakup rekomendasi untuk standardisasi praktik dropship syariah dan peningkatan mekanisme adopsi fatwa ke dalam regulasi formal untuk memperkuat ekosistem e-commerce syariah yang berkelanjutan. Kata kunci: Dropship, E-commerce, Fatwa DSN-MUI, Shopee, Ekonomi Syariah, Sosiologi Antropologi Hukum